Geser untuk Memilih: Studi Kuantitatif tentang Media Sosial dan Perilaku Politik Generasi Z pada Pemilihan Gubernur Sumatera Barat Tahun 2024 - Lusi Puspika Sari; Ilham Havifi; Vivi Desrianti Putri; Muhammad Dzaky Ramadhan (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2026)
The 2024 West Sumatra gubernatorial election offers a critical site for understanding the political behavior of Generation Z, a cohort raised in the digital era, for whom social media is both the primary source of political information and a space for spontaneous, often viral political expression. This study examines the relationship between the intensity of political content consumption on social media and the political behavior of Generation Z in West Sumatra across cognitive, affective, and conative dimensions. Using an online survey of respondents aged 17–27 with proportionate stratified random sampling, thestudy applies correlation and simple linear regression analysis. The findings reveal a strong, significant association between social media use and Generation Z’s political behavior (significance value 0.000; calculated t = 16.380, exceeding the critical value), and a positive regression coefficient (1.925) indicates that higher consumption is positively correlated with political behavior. Cognitively, most respondents showed adequate political knowledge but remained neutral toward information credibility, reflecting digital caution and high fact-checking awareness. Affectively, they expressed strong interest in politicalissues and rational support for public policies while keeping a critical distance from political actors and institutions. The association with political action is dualistic: it accompanies high electoral participation but does not fully stimulate digital activism. Social media thus plays an important role in shaping political awareness yet has not become a driver of non-electoral participation, indicating a need for further research on how political identity relates to political behavior.